Realism in fiction and Howells' relation to it - Smith, Marietta (My University, 1895)
Introduction: We are ever told that “truth is stranger than fiction”, ad as we come to realize the truths of life we believe the saying more and more firmly. If primitive man, who attempted to explain the phenomena of life and death, the phenomena of disease, disaster, and storm by the presence of spirits and gods, had known the true causes he would have most devoutly believed “truth to be stranger than the fiction” which he created. When the story tellers took for their models the kind and his court, the stories assumed such an imaginative form, for the purpose of pleasing the models, that reality was lost sight of. But with the passing of the age of chivalry and of minstrels the fairytale gave place to stories of humanity. Each age has produced the literature which satisfied its demands, and the realism of today is the result of the doubt of the age. The age which has produced realism, we can say with Bates, was “an age in which existed a mighty spirit of doubt and negation, and such a period is slow to trust itself to any guide save cold-blooded veracity.”
Citation: Smith, Marietta. Realism in fiction and Howells' relation to it. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: English; Fiction; Realism; Theses; Manuscripts (documents)